Tree‐ring‐based temperature reconstruction for the northern Greater Higgnan Mountains, China, since A.D. 1717. (20th February 2012) - Zhang, Tongwen; Yuan, Yujiang; Wei, Wenshou; Yu, Shulong; Zhang, Ruibo; Shang, Huaming; Chen, Feng; Fan, Zi'ang; Qin, Li
Abstract: In this paper, ring‐width chronologies of pine trees ( Pinus sylvestris var. mongolica ) from one sampling site in the northern Greater Higgnan Mountains, China, were constructed. The results of growth‐climate responses show that mean temperature is the limiting factor affecting radial growth of pine trees in the study area. Consequently, mean temperature from May to October from 1717 to 2008 has been reconstructed using the standard chronology. For the calibrated period (1957‐2008), the explained variance of the reconstruction is 57%. The characteristics of the reconstruction expose that mean temperature has increased since the 1970s, and the decade 2000s and 1990s are also ranked as the warm decades on record. However, this period from 1970s to now is not exceptional within the past 300 years. By applying an 11‐year moving average to the reconstruction, three warm periods and three cold periods are evident. The warm and cold periods of the reconstructed mean temperature correspond well with other reconstructions. Power spectral and wavelet analysis demonstrated the existence of significant ∼70‐ and ∼100‐year cycles of variability. Furthermore, the reconstruction and North Atlantic Oscillation Index showed a significant positive correlation ( r = 0.34, n = 136, p < 0.0001). Copyright © 2012 Royal Meteorological Society